Between expert and student perspectives: on the intersection of affect and heuristic-didactic discourse in the undergraduate classroom. Issue 1 (2nd January 2023) - Marmur, Ofer; Koichu, Boris
ABSTRACT: This paper explores student emotion and learning experiences fostered by lecturing-style instruction in Real-Analysis problem-centered lessons. We focus on two lessons that were taught by two reputable instructors and involved challenging, mathematically-related problems the students did not understand. Nonetheless, one lesson evoked negative emotional reactions, while the other positive emotional reactions – a phenomenon we aimed at explaining. The main data comprise the filmed lessons and subsequent stimulated-recall interviews with nine students. The analysis draws on conceptual tools from three perspectives: mathematical discourse, variation theory, and a recently developed construct of key memorable events (KMEs) that offers an affective-cognitive lens for investigating the interrelation between teaching and learning. The findings indicate that the positively-perceived lesson contained instances of what we call heuristic-didactic discourse : a meta-level discourse that presents heuristics monitored from an expert's perspective, yet derived from a student's perspective. Implications for research and practice are drawn.